2016
DOI: 10.1155/2016/9849087
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reorganizations of Brain Network in Prelingually Deaf Adolescents

Abstract: Previous neuroimaging studies suggested structural or functional brain reorganizations occurred in prelingually deaf subjects. However, little is known about the reorganizations of brain network architectures in prelingually deaf adolescents. The present study aims to investigate alterations of whole-brain functional network using resting-state fMRI and graph theory analysis. We recruited 16 prelingually deaf adolescents (10~18 years) and 16 normal controls matched in age and gender. Brain networks were constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Increased resting-state functional connections were reported between the right superior parietal gyrus (rSPG) and the right insula, and between the middle temporal gyrus and the posterior cingulate gyrus (2016). In the same study, Li et al (2016) also reported an altered arrangement of highly interconnected functional hubs.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 73%
“…Increased resting-state functional connections were reported between the right superior parietal gyrus (rSPG) and the right insula, and between the middle temporal gyrus and the posterior cingulate gyrus (2016). In the same study, Li et al (2016) also reported an altered arrangement of highly interconnected functional hubs.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 73%
“…However, to the best of our knowledge, no direct mapping of the tonotopic, or topographic, organization was conducted in the CI-naïve congenitally deaf human auditory cortex, let alone in its association regions, without any auditory sensory experience. On the other hand, there is evidence for plasticity in this population: there are clear changes in white matter and gray matter volumes and correlation in early auditory cortex 93 94 95 , and changes in functional connectivity of the auditory cortex 9 96 97 . Such changes tend to emphasize cross-modal compensatory plasticity, especially with regard to language.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of ERPs, calculating partial directed coherence (PDC) based on such time-variant multivariate autoregressive models and measures as centrality or modularity have emerged as useful tools for assessing connectivity between different brain locations ( Schelter et al, 2006 ; Keller et al, 2014 ; Rodrigues and Baccalá, 2015 ). Recently, graph theory-based methods have been used to explore the cortical reorganization of functional networks in prelingual deaf adolescents ( Li et al, 2016 ). Indeed, ERPs and graph analyses are complementary, not mutually exclusive techniques (eg., Mutlu et al, 2012 ) that can contribute to a better understanding of how profoundly deaf individuals learn to discriminate sound using a novel sensory pathway.…”
Section: Introductionmentioning
confidence: 99%